EGF-coated gold nanoparticles provide an efficient nano-scale delivery system for the molecular radiotherapy of EGFR-positive cancer. (1st November 2016) - Song, Lei; Falzone, Nadia; Vallis, Katherine A.
Abstract: Purpose Radiolabeled antibodies and peptides hold promise for molecular radiotherapy but are often limited by a low payload resulting in inadequate delivery of radioactivity to tumour tissue and, therefore, modest therapeutic effect. We developed a facile synthetic method of radiolabeling indium-111 ( 111 In) to epidermal growth factor (EGF)-gold nanoparticles ( 111 In-EGF-Au NP) with a high payload. Materials and methods EGF-Au NP were prepared via an interaction between gold and the disulphide bonds of EGF and radiolabeled using 111 InCl3 . Targeting efficiency was investigated by quantitating internalized radioactivity and by confocal imaging following exposure of MDA-MB-468 (1.3 × 10 6 EGFR/cell) and MCF-7 (10 4 EGFR/cell) cells to Cy3-EGF-Au NP. Cytotoxicity was evaluated in clonogenic assays. Results The proportion of total administered radioactivity that was internalized by MDA-MB-468 and MCF-7 cells was 15% and 1.3%, respectively (mixing ratio of EGF:Au of 160). This differential uptake in the two cell lines was confirmed using confocal microscopy. 111 In-EGF-Au NP were significantly more radiotoxic to MDA-MB-468 than MCF-7 cells with a surviving fraction of 17.1 ± 4.4% versus 89.8 ± 1.4% ( p < 0.001) after exposure for 4 h. Conclusions An 111 In-labeled EGF-Au nanosystem was developed. It enabled targeted delivery of a high 111 In payload specifically to EGFR-positive cancer cells leading to radiotoxicity that can be exploited for molecularly targeted radiotherapy.